Senior High School Student’s Perception of Limiting Factors Affecting The Implementation of Remote Teaching Process - Krisna Karunika, Kadek (Universitas Pendidikan Ganesha, 2022)
Since the Covid-19 Pandemic, the learning system in Indonesia has changed to remote teaching. Many students, especially in Senior High School, needed help implementation of the online learning process with this remote teaching. This study aims to analyse students’ perceptions of the factors that become obstacles in remote teaching. There have been many researchers who have examined this case but have yet to use one research method. Therefore, researchers want to present different data using mixed methods (Qualitative & Quantitative), which are more dominant in qualitative method. When the data is collected to be analyzed, the qualitative method uses a matrix literature review and an interview guide. In contrast, the quantitative method uses a questionnaire to obtain more valid data. The data that have obtained will analyze quantitatively. The results of this study show that there are five limiting factors in the implementation of the remote teaching process such as (1) inexperienced students, (2) inadequate online learning facility, (3) unreliable internet connection, (4) deficient interaction, and (5) insufficient parental support. And there are factors that limiting of the remote teaching process that three informants have mentioned.